Gingival Enlargement Management in Bir Hospital – A Case Series - Koirala, Pramod Kumar; Pradhan, Shaili; Gorkhali, Ranjita Shrestha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
An increase in size of gingiva is a common clinical condition termed as gingival overgrowth. The definite aetiology is unknown. It is classified on the basis of aetiologic factors and pathologic changes. Both localised and generalised overgrowth are encountered commonly and patients are aesthetically, socially, psychologically and functionally disturbed until they revert back to the original contour. Localised gingival enlargement frequently is inflammatory and can also be associated with systemic diseases/condition (hormonal, nutritional, allergic, nonspecific conditioned) or neoplasic and sometimes false enlargement. DIGO is a well documented side effect with the use of anticonvulsant, immunosuppressant, and calcium channel blockers. Total 3% to 84.5% of subjects taking these drugs seem to have significant enlargement. Localised overgrowth are managed by proper diagnosis followed by controlling inflammation and other causative factors before surgical excision. DIGO is managed by drug replacement and surgical excision if required after nonsurgical treatment. Gingivoplasty of gingival margin is necessary to create self-cleansing and aesthetic architecture.